2010
DOI: 10.1158/0008-5472.can-10-0824
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4α Suppresses the Development of Hepatocellular Carcinoma

Abstract: Hepatocyte nuclear factor 4α (HNF4α) is a transcription factor that plays a key role in hepatocyte differentiation and the maintenance of hepatic function, but its role in hepatocarcinogenesis has yet to be examined. Here, we report evidence of a suppressor role for HNF4α in liver cancer. HNF4α expression was progressively decreased in the diethylinitrosamine-induced rat model of liver carcinogenesis. In human liver tissues, HNF4α expression was decreased in cirrhotic tissue and further decreased in hepatocarc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
233
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(269 citation statements)
references
References 37 publications
24
233
1
11
Order By: Relevance
“…6A). HNF4A exhibited the strongest enrichment for binding near genes down-regulated in cancer, in agreement with previous observations implicating it as a tumor suppressor gene (Ning et al 2010;Bonzo et al 2012). GABPA and SP1 showed strong enrichment (FDR < 0.05) for binding near genes up-regulated in tumor tissue.…”
Section: Disruption Of Dap Activity In Hepatocellular Carcinomasupporting
confidence: 90%
“…6A). HNF4A exhibited the strongest enrichment for binding near genes down-regulated in cancer, in agreement with previous observations implicating it as a tumor suppressor gene (Ning et al 2010;Bonzo et al 2012). GABPA and SP1 showed strong enrichment (FDR < 0.05) for binding near genes up-regulated in tumor tissue.…”
Section: Disruption Of Dap Activity In Hepatocellular Carcinomasupporting
confidence: 90%
“…It has been shown that the majority of de-differentiated hepatoma cell lines and tissues fail to express HNF4a, but forced expression of this factor is sufficient to re-express a set of hepatocyte marker genes and restore the epithelial morphology of these cells (Späth and Weiss, 1998;Tanaka et al, 2006), which implies that it plays a role in the regulation of EMT. Moreover, forced expression of HNF4a completely induces the differentiation of hepatoma cells into hepatocytes in mice and blocks hepatocarcinogenesis in rats (Ning et al, 2010;Yin et al, 2008). However, the molecular mechanisms by which HNF4a maintains the differentiated liver epithelium and inhibits EMT have not been completely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alterations in HNF4␣ functionality may increase the risk for development of HCC. Indeed, several mouse and human studies have shown that HNF4␣ expression is diminished in HCC (15)(16)(17)(18). Additionally, it was demonstrated that overexpression of HNF4␣ in rodent HCC models blocks carcinogenesis and metastasis, thus indicating a potential role for HNF4␣ as a tumor suppressor (16,19).…”
mentioning
confidence: 99%